2017
DOI: 10.1038/s41598-017-12859-6
|View full text |Cite
|
Sign up to set email alerts
|

Worsening calcification propensity precedes all-cause and cardiovascular mortality in haemodialyzed patients

Abstract: A novel in-vitro test (T50-test) assesses ex-vivo serum calcification propensity which predicts mortality in HD patients. The association of longitudinal changes of T50 with all-cause and cardiovascular mortality has not been investigated. We assessed T50 in paired sera collected at baseline and at 24 months in 188 prevalent European HD patients from the ISAR cohort, most of whom were Caucasians. Patients were followed for another 19 [interquartile range: 11–37] months. Serum T50 exhibited a significant declin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 33 publications
0
33
1
Order By: Relevance
“…A nanoparticle-based assay was developed, which detects the influence of serum on spontaneous transformation of primary CPPs into secondary CPPs and, thus, the balance between inhibitors and promoters of calcification in the serum [ 12 ]. Serum calcification propensity was suggested as a biomarker for cardiovascular disease [ 163 ] and shown to predict cardiovascular and all-cause mortality in CKD [ 164 , 165 ].…”
Section: Signaling Pathways Regulating Vsmcs Calcification During Higmentioning
confidence: 99%
“…A nanoparticle-based assay was developed, which detects the influence of serum on spontaneous transformation of primary CPPs into secondary CPPs and, thus, the balance between inhibitors and promoters of calcification in the serum [ 12 ]. Serum calcification propensity was suggested as a biomarker for cardiovascular disease [ 163 ] and shown to predict cardiovascular and all-cause mortality in CKD [ 164 , 165 ].…”
Section: Signaling Pathways Regulating Vsmcs Calcification During Higmentioning
confidence: 99%
“…Furthermore, the accumulation of fetuin-A-containing mineral particles was noted in the peritoneal dialysate of a patient suffering from calcifying peritonitis [10] and in patients suffering from chronic kidney disease (CKD) [11]. Recent work has shown that both the abundance of CPP [12][13][14] and the kinetics of CPP formation [15][16][17][18] in serum of CKD patients can be used to monitor the propensity for calcification of these patients. The function of fetuin-A as an inhibitor of calcification is underscored by clinical studies showing that low fetuin-A serum levels are associated with calcification disease [19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…An association of shorter T 50 times with increased all-cause and CV mortality, as well as CV events, could be demonstrated in pre-dialysis CKD patients, HD patients, and KTR (Table 6) [76,107,[116][117][118]. Aortic pulse wave velocity (APWV), as a quantification tool of progressive arterial stiffness and vascular calcification, showed conflicting results in association with T 50 [116,118].…”
Section: Clinical Associationmentioning
confidence: 99%
“…Mean: 212 min (10th-90th percentile: 109-328 min) 1.7 Association of low T50 with increased all-cause mortality and CVD [117] HD patients (n = 188) Mean: 246 ± 64 min 3.7…”
Section: Follow Up Years Findingsmentioning
confidence: 99%